The Influence Of Work Discipline, Work Effectiveness And Work Environment On Employee Performance Village In East Seluma District Seluma District - Saputra, Niko; Anggriani, Ida; Wijaya, Ermy (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2025)
The purpose of this research is to determine the influence of work discipline and work effectiveness and the work environment on the performance of subdistrict employees in East Seluma District, Seluma Regency. The data collection method in this research used a questionnaire technique, with a sample of 45 respondents. The research results show that multiple linear regression Y = 1.806 + 0.361 X1 + 0.537 X2 + 0.151 X3 + 1.567. Where the coefficient is positive, it means that there is a positive or unidirectional relationship between the variables of work discipline, work effectiveness and work environment on the performance of local employees in Seluma Tmur District, Seluma Regency. The results show that the results of the work discipline test (XI) show tcount 2,249 > ttable 1,679 and significance 0.030 < 0.05, so the results of the hypothesis Ha are accepted and Ho is rejected, meaning that work discipline (XI) has a positive and significant effect on the performance of subdistrict employees in the District Seluma Seluma Regency. The results of the work effectiveness test (X2) show that tcount is 3.514 > ttable 1.679 and the significance is 0.001 < 0.05, so the results of the Ha hypothesis are accepted and Ho is rejected, meaning that work effectiveness (X2) has a positive and significant effect on the performance of sub-district employees in East Seluma District, Regency. Seluma. The results of the work environment test (X3) show tcount 2,566 > ttable 1,679 and significance 0.014 < 0.05, so the results of the Ha hypothesis are accepted and Ho is rejected, meaning the work environment (X3) has a positive and significant effect on the performance of sub-district employees in East Seluma District, Regency Seluma. Based on the comparison of the Fcount value with Ftable, the Fcount value is greater than the Ftable value, namely 32,214 > 2.81, so it is concluded that the hypothesis is accepted, meaning that there is a simultaneous influence between work discipline (XI), work effectiveness (X2), work environment (X3) on performance. sub-district employee (Y) in Seluma District, Seluma Regency. This can be seen at the significance level of 0.000 <0.05